Comparative Study of Short Video and E-Booklet Media in Enhancing Students’ Understanding of Traffic Safety - Uktolseja, Goklas Hendra; Brilianti, Dani Fitria; Basuki, Ahmad; Purwanto, Edi (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to analyze the effectiveness of learning media in the form of short videos and e-booklets in improving students' understanding of traffic safety among ninth-grade students at SMP Negeri 7 Samarinda. This study employs a quantitative approach using a quasi-experimental method and a pre-test and post-test control group design. Data were collected through comprehension tests administered before and after the intervention, supplemented by interviews, observations, and documentation as primary data. Additionally, secondary data were gathered through relevant literature reviews to strengthen the theoretical foundation and analysis. The population in this study consisted of 871 students, and 60 students were selected as samples using purposive sampling. The samples were divided into two equal groups, the first group using short video media and the second group using e-booklet media in learning. Data were analyzed using the Liliefors normality test and the Independent Samples T-Test. The results of the study indicate that both media contribute positively to improving student understanding. Although the difference between the two media is not statistically significant, the average understanding score of students in the short video group is higher than that of the e-booklet group. Thus, it can be concluded that short video media tends to be more effective in practice in improving students' understanding of traffic safety compared to e-booklets. Therefore, teachers and educators are advised to optimize the use of short videos as an attractive, concise, and interactive learning medium.